PPO.01 EQUIPP: Evaluation of Fetal Fibronectin with a novel bedside Quantitative Instrument for the Prediction of Preterm birth. (9th June 2014) - Abbott, DS; Hezelgrave, NL; Seed, PT; Bennett, PR; Chandiramani, M; David, AL; Girling, J; Norman, JE; Stock, SJ; Tribe, RM; Shennan, AH
Abstract : Introduction: Fetal fibronectin (fFN) is a leading predictor of spontaneous preterm birth (sPTB) in high-risk asymptomatic women. As a positive/negative test (threshold of 50 ng/mL) the negative predictive value is high but positive predictive value (PPV) modest. The EQUIPP study aimed to determine if quantitative analysis of fFN (qfFn) improved prediction. Methods: A prospective masked observational study (n = 1387) of high-risk asymptomatic women who underwent qfFN testing between 22 +0 – 27 +6 weeks' gestation at 5 UK centres. Primary endpoint: sPTB <34 weeks'. Results: sPTB rate <34 weeks' was 7.1%. Only 2.8% (26/941) of women with qfFN concentration < 10 ng/mL delivered <34 weeks'. The PPV for sPTB <34 weeks' increased from 16.6%, 24.1%, 36.8%. 45.0% with increasing thresholds (10, 50, 200, and 500 ng/mL) respectively. Compared with qfFN <10 ng/mL, the relative risk of sPTB was 3.8 (95% CI, 2.3–6.6), 5.7 (3.2–10.0), 12.3 (7.3–20.8) and 16.3 (8.8–30.1) (p < 0.0001). The area under the Receiver Operating Characteristic curve for sPTB <34 weeks' was 0.79 (0.74–0.84). Women with a short cervix on ultrasound (<25 mm) had a ten-fold increase in sPTB with qfFN concentration ≥200 ng/mL (18/45, 40%) vs. qfFN <10 ng/mL (3/68, 4.4%). Conclusion: qfFN provides alternative thresholds to define risk of sPTB compared with qualitative assessment. For high-risk women with qfFN <10 ng/mL (68% of cohort) risk of sPTB equalled background risk (3.3%) providing reassurance and potential discharge from intensive surveillance. qfFN ≥200 ng/mL offers improved positive prediction over conventional testing and is a valuable tool for risk assessment in women with a short cervix.